Design and construction of an IoT-based solar panel batteray monitoring system for household needs - Ardiyanto, Kevin; Maulindar, Joni; Dwiirawan, Ridwan (Politeknik Negeri Lhokseumawe, 2025)
This study aims to design and build a solar panel battery monitoring system based on the Internet of Things (IoT) for household needs. Given the increasing demand for energy and reliance on fossil fuels, this system addresses the challenges of monitoring the performance and status of solar panel batteries. The methods employed include measuring electrical current using the ACS712 sensor, controlling a 5V water pump, and programming the ESP32 module. The research results indicate a reduction in water usage by up to 30%, with the watering frequency decreasing from three times to two times per day, thereby enhancing resource efficiency. Data visualization through a PCB dot matrix allows users to understand the system status in real-time. Despite limitations related to internet connectivity, this study makes a significant contribution to the development of IoT technology in the field of renewable energy and opens avenues for further research.